2010
DOI: 10.1002/ejic.201000753
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Water‐Soluble Hexanuclear Bismuth Oxido Cluster – Synthesis, Structure and Complexation with Polyacrylate

Abstract: The reaction of [Bi6O4(OH)4](NO3)6·H2O with triflic acid gave colorless single crystals of [Bi6O4(OH)4(OTf)6(CH3CN)6]·2CH3CN (1) upon crystallization from acetonitrile/chloroform. Compound 1 crystallizes in the monoclinic space group P21/n. The novel hexanuclear bismuth oxido cluster is highly soluble in water and polar organic solvents. A transparent and water‐soluble hybrid material was obtained by reaction of [Bi6O4(OH)4(OTf)6(CH3CN)6]·2CH3CN (1) with polyacrylate in aqueous solution. Molecular dynamics sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 44 publications
2
47
1
Order By: Relevance
“…Additionally, partially hydrolyzed bismuth oxido clusters such as [Bi 38 O 45 A C H T U N G T R E N N U N G (hfac) 24 ] (hfac = hexafluoroacetylacetonate) and [Bi 38 O 45 A C H T U N G T R E N N U N G (OMc) 24 A C H T U N G T R E N N U N G (DMSO) 9 ]·2 DMSO·7 H 2 O (OMc = methacrylate) were reported among others. [12][13][14][15][16][17][18][19] Previously, we described a soluble bismuth oxido cluster, [Bi 22 O 26 (OSiMe 2 tBu) 14 ] (1), which was isolated almost quantitatively as the product of partial hydrolysis of the respective bismuth silanolate. [17] This was the first example to demonstrate the structural relationship between bismuth oxido clusters and bulk bismuth oxide as final hydrolysis/condensation product.…”
Section: A C H T U N G T R E N N U N G (Me 2 Co) 5 ]·15 Me 2 Co and mentioning
confidence: 99%
“…Additionally, partially hydrolyzed bismuth oxido clusters such as [Bi 38 O 45 A C H T U N G T R E N N U N G (hfac) 24 ] (hfac = hexafluoroacetylacetonate) and [Bi 38 O 45 A C H T U N G T R E N N U N G (OMc) 24 A C H T U N G T R E N N U N G (DMSO) 9 ]·2 DMSO·7 H 2 O (OMc = methacrylate) were reported among others. [12][13][14][15][16][17][18][19] Previously, we described a soluble bismuth oxido cluster, [Bi 22 O 26 (OSiMe 2 tBu) 14 ] (1), which was isolated almost quantitatively as the product of partial hydrolysis of the respective bismuth silanolate. [17] This was the first example to demonstrate the structural relationship between bismuth oxido clusters and bulk bismuth oxide as final hydrolysis/condensation product.…”
Section: A C H T U N G T R E N N U N G (Me 2 Co) 5 ]·15 Me 2 Co and mentioning
confidence: 99%
“…[7] Empirical interaction potentials were employed for describing the ion-ion [5] and the ion-solvent and solvent-solvent interactions. [8,9] To mimic a bulk DMSO solution, a cubic cell of 850 DMSO molecules was subjected to periodic boundary conditions.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…Our previous investigations towards the functionalization of [Bi 6 O 4 (OH) 4 ](NO 3 ) 6 ‧H 2 O showed that, in toluene solution, an exchange of the nitrate ligands for trifluoromethanesulfonate to give [Bi 6 O 4 (OH) 4 (OTf) 6 ] does occur (Miersch et al, 2010). If DMSO is used as a solvent, we did observe a growth of the hexanuclear bismuth oxido cluster to give Bi 38 -oxido clusters such as [Bi 38 O 45 (Miersch et al, 2011a(Miersch et al, ,b, 2012.…”
Section: Resultsmentioning
confidence: 99%